2015
DOI: 10.1167/iovs.14-16211
|View full text |Cite
|
Sign up to set email alerts
|

Fundus Autofluorescence Characteristics of Nascent Geographic Atrophy in Age-Related Macular Degeneration

Abstract: Fundus autofluorescence imaging revealed that areas of nGA were most commonly characterized by both hyper- and hypoautofluorescent changes, which differs from areas of drusen-associated atrophy that most often appeared hypoautofluorescent. These findings provide important insights into the FAF characteristics of areas undergoing atrophic changes in eyes still considered to be in the early stages of AMD by current methods, and thus assist in the characterization of disease severity in these early stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 36 publications
3
51
1
Order By: Relevance
“…21 Also, as shown by Wu et al, atrophy of the RPE and overlying photoreceptors on SDOCT immediately preceded new onset of drusen-associated GA on CP. 22,23 Briefly, these findings suggested that SDOCT is useful to visualize early indicators of atrophy, rather than neovascularization. 1421 In an attempt to further clarify the sequence of degenerative events in the atrophic pathway, we focused this report on the A2A SDOCT Study aims pertinent to atrophy and its possible precursors.…”
mentioning
confidence: 99%
“…21 Also, as shown by Wu et al, atrophy of the RPE and overlying photoreceptors on SDOCT immediately preceded new onset of drusen-associated GA on CP. 22,23 Briefly, these findings suggested that SDOCT is useful to visualize early indicators of atrophy, rather than neovascularization. 1421 In an attempt to further clarify the sequence of degenerative events in the atrophic pathway, we focused this report on the A2A SDOCT Study aims pertinent to atrophy and its possible precursors.…”
mentioning
confidence: 99%
“…24 Using high-resolution multimodal imaging, in particular spectral-domain optical coherence tomography (SD-OCT) and confocal scanning laser ophthalmoscopy (cSLO) fundus autofluorescence (FAF), the evolution of atrophy has been scrutinized in more detail. 23,[25][26][27][28] Among those observations, ''nascent GA'' as part of the chronological appearance of drusen-associated atrophy development has been analyzed by Wu et al 26 Recently, the Classification of Atrophy Meetings (CAM) group defined OCT-based criteria for complete RPE and outer retinal atrophy (cRORA) as atrophy in AMD. 29 The aim of the current study was to analyze the incidence and development of central atrophy in AMD eyes that were considered at high risk for development of late AMD stages.…”
mentioning
confidence: 99%
“…15 It is also recognized that subtle changes in microstructural features occur in the early stages of AMD, despite not easily appreciated on clinical examination or on CFPs. 16,17 Such changes can be visualized and quantified on high-resolution imaging modalities such as SD-OCT, including changes to the extent and morphology of drusen, 4,8,9,[18][19][20][21] pigmentary abnoriovs.arvojournals.org j ISSN: 1552-5783 malities, 6 atrophic changes (including nascent GA [nGA] 7,22 and drusen-associated atrophy) and the integrity of the photoreceptor inner-segment ellipsoid (ISe) band. 19 Previous studies have also observed that changes in some of these microstructural features are strongly associated with changes in mesopic microperimetric sensitivity, although it is not possible to conclude whether any of these parameters represent the underlying pathologic changes that are contributing to the decreased visual sensitivity.…”
mentioning
confidence: 99%
“…This study, therefore, examined the associations between visual function changes on mesopic microperimetry and longitudinal changes in SD-OCT microstructural parameters, including drusen volume, pigmentary changes (visualized on SD-OCT as hyperreflective foci [HF] 28 ) and its inner retinal migration and proliferation, 6 and atrophic changes (including nGA and drusen-associated atrophy detected on SD-OCT 7,22 ) in participants with the early stages of AMD. All these parameters have been observed to be significantly associated with the future development of advanced AMD, [6][7][8][9] and may therefore be independently associated with the longitudinal rate of change in microperimetric sensitivity.…”
mentioning
confidence: 99%